Purely Lifting Module - Gareeb, Najmaddin H.; Al-Bahraany, Bahar H. (Sulaimani Journal for Pure and Applied Sciences, 2007)
In this paper we will generalize the concept of a lifting module. various properties and characterizations of a general case; the pure lifting module, are established and some other known results has been generalized
Keywords: Pure and small submodules; Lifting; regular; hollow; multiplication; prime; faithful; and cancellation modules